VD_FINDINFO Décision / 2012 / 970 vom 3. August 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, MISE EN LIBERTÉ PROVISOIRE, PROLONGATION | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 228 CPP (CH), 393 al. 1 let. c CPP (CH)